Processamento e restituição digital de fotografias aéreas coloridas para estudo da cobertura vegetal - Souza, Sara [UNESP]; Barros, Zacarias Xavier de [UNESP]; Bosco, João [UNESP]; Campos, Sérgio [UNESP]; Cardoso, Lincoln Gehring [UNESP] (My University, 2011)
This work aimed to apply geoprocessing techniques to identify and to quantify the types of vegetal coverings in part of the county Botucatu – SP, having been divided into three phases: acquisition of data; georeferencing based on the digital topographic maps in 1:50000 scale and finally the thematic maps were generated. The methodology used to the analogical aerial photographics georeferencing showed efficient, considering that it was based on scientific procedures of residues analysis and the positioning central was classified as A, according to the Cartographic Precision Pattern.

O presente estudo utilizou técnicas de geoprocessamento para identificar, verificar a qualidade posicional da área e quantificar a cobertura vegetal encontrada em parte do município de Botucatu – SP, desta forma o mesmo foi dividido em três fases: aquisição dos dados, georreferenciamento baseado em cartas planialtimétricas no formato digital escala 1:50000 e confecção das cartas temáticas. A metodologia utilizada para o georreferenciamento das fotografias aéreas analógicas mostrou-se eficiente uma vez que a mesma foi baseada em fundamentos científicos de análise de resíduos e o controle posicional foi classificado como A, segundo o Padrão de Exatidão Cartográfica.
Processing and Digital processing of colored aerial photography for study of the vegetable covering
Keywords: Geoprocessamento; Imagens aéreas; Cartas temáticas; Geoprocessing; Aerial images; Thematic maps